Atmospheric deposition of glacial iron in the Gulf of Alaska impacted by the position of the Aleutian Low. Issue 10 (29th May 2017) - Schroth, Andrew W.; Crusius, John; Gassó, Santiago; Moy, Christopher M.; Buck, Nathan J.; Resing, Joseph A.; Campbell, Robert W.
Abstract: Our understanding of glacial flour dust storm delivery of iron to the Gulf of Alaska (GoA) is limited. Here we interpret concurrent time series satellite, meteorological, and aerosol geochemical data from the GoA to examine how interannual variability in regional weather patterns impacts offshore aerosol glacial Fe deposition. In 2011, when a northerly Aleutian Low (AL) was persistent during fall, dust emission was suppressed and highly intermittent due to prevalent wet conditions, low winds, and a deep early season snowpack. Conversely, in 2012, frequent and prolonged fall dust storms and high offshore glacial Fe transport were driven by dry conditions and strong offshore winds generated by persistent strong high pressure over the Alaskan interior and Bering Sea and a southerly AL. Twenty‐five‐fold interannual variability in regional offshore glacial aerosol Fe deposition indicates that glacial dust's impact on GoA nutrient budgets is highly dynamic and particularly sensitive to regional climate forcing. Key Points: Large‐scale interannual variabilities in the aeolian transport of glacial iron to offshore regions of the Gulf of Alaska are detected Aleutian Low position drives magnitude of glacial Fe dust transport to northern Gulf of Alaska in fall Rapid changes in weather can produce dust storms and significant offshore Fe deposition even during very wet seasons